The Hibrid Method Determinative Magnetic Fields of DY - Matuliauskas, R. (Elektronika ir Elektrotechnika, 2004)
It is very widely known method to search magnetic field (MF) values in the area between 3-D netting points where was havingmeasured MF. According new method MF distribution in this space is found theoretically used only measurements of MF values werefulfilled only in the 2-D netting points of the surface covering the 3-D space. There are have presented comparison results of thecalculation and empirically datas of deflection yoke VV2920. Ill. 5, bibl 7 (in English; summaries in Lithuanian, English and Russian).